UPAYA ADMINISTRATIF DALAM PENYELESAIAN SENGKETA KEPEGAWAIAN ASN AKIBAT PENJATUHAN HUKUMAN DISIPLIN - Anggoro, Firna Novi (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2022)
The imposition of disciplinary punishment often creates disputes between ASN and officials authorized to impose sentences so that even the imposition of punishment can be a unilateral legal action. This is where the ASN staffing dispute arises. Regarding ASN employment disputes arising from the imposition of disciplinary punishment, it is necessary to understand the efforts that can be taken by ASN in dealing with actions taken by the state administration agency or official. The problem is what are the arrangements and mechanisms for administrative review in resolving ASN disputes due to disciplinary punishment and what is the role of administrative review in resolving ASN staffing disputes due to disciplinary punishment. This research is a normative juridical research with a statute approach and a conceptual approach. The ASN Law states that ASN employee disputes are resolved through further administrative review. Arrangements and Mechanisms for Administrative review in Settlement of ASN Personnel Disputes Due to Disciplinary Punishments are regulated in the Civil Servant Discipline PP and PP Administrative review and BPASN. Administrative review are a form of legal protection (rechtsbescherming) for ASN, as well as functioning as oversight (internal, a-posteriori) of the actions of government organs